The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.2190/djh3-y4r0-r3kg-jycc
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Early Adherence to the Antidepressant Citalopram among Older Primary Care Patients: The Prospect Study

Abstract: Objective-Our purpose was to determine the personal characteristics associated with different patterns of adherence to the antidepressant citalopram in a primary care trial of depression management.Method-The study sample consisted of 228 adults aged 60 years and older recruited from primary care settings and who participated in a depression intervention. The intervention consisted of services of trained care managers, who offered recommendations to physicians following a clinical algorithm and helped patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…However, the methodology of this study, which included both depressed and non-depressed subjects did not allow the investigators to determine whether the differences in adherence rates by race were due to 1) lower diagnosis or prescription rates by providers, or 2) lower rates of initiation and adherence by African-American subjects. Another study using data from a collaborative care intervention (PROSPECT) found that non-White race was the factor most strongly associated with non-adherence to citalopram [52]. Finally, in a study comparing African-American (n=49) to Latino (n=52) subjects over the age of 55 who had been prescribed antidepressants in the prior year, Ayalon et al found that 52.6% of African-American subjects were non-adherent, similar to the number found in our study [53].…”
Section: Discussionmentioning
confidence: 99%
“…However, the methodology of this study, which included both depressed and non-depressed subjects did not allow the investigators to determine whether the differences in adherence rates by race were due to 1) lower diagnosis or prescription rates by providers, or 2) lower rates of initiation and adherence by African-American subjects. Another study using data from a collaborative care intervention (PROSPECT) found that non-White race was the factor most strongly associated with non-adherence to citalopram [52]. Finally, in a study comparing African-American (n=49) to Latino (n=52) subjects over the age of 55 who had been prescribed antidepressants in the prior year, Ayalon et al found that 52.6% of African-American subjects were non-adherent, similar to the number found in our study [53].…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Our conceptual framework, adapted from Cooper and colleagues, 17 is practical in its approach and provided a framework that allowed for fl exible, tailored interventions ( Figure 1). Our intervention addressed each factor resulting in nonadherence in the conceptual model by means of a multifaceted, individualized approach in which participants worked with the integrated care manager to develop strategies to overcome barriers to adherence to medications.…”
Section: Introductionmentioning
confidence: 99%
“…In elderly adults, Bogner et al (2006) found that even after controlling for education, ethnic minority status predicted adherence as measured by pill counts, such that Whites were more likely to be adherent to taking their antidepressant. After controlling for a host of confounding variables, Diaz et al (2005) found that monolingual Hispanic and AfricanAmerican patients had lower medication adherence rates than did NonHispanic Whites.…”
Section: S Department Of Health and Human Services 2001; Freedenthanmentioning
confidence: 99%